Birth order and human capital development: Evidence from Ecuador - Monique de Haan; Erik Plug; José Rosero (Institute for the Study of Labor (IZA), 2012)
In this paper we examine the effect of birth order on human capital development in Ecuador using a large national database together with self-collected survey data. Using family fixed effects models we find significant positive birth order effects; earlier born children stay behind in their human capital development from early childhood to adolescence. Turning to potential mechanisms we find that earlier born children receive less quality time from their mothers than later born children. In addition, they are breastfed shorter. The estimated birth order effects are largest for children in their teens growing up in poor, low educated families.
Keywords: D1; I2; J1; 330; birth order; human capital development; parental time allocation; Ecuador; Kinder; Bildungsinvestition; Eltern; Zeitverwendung; Ecuador